Wohlstand neu denken und messen - Jakob Dirksen; Katharina Lima de Miranda (Wirtschaftsdienst, 2023)
– Addressing the major challenges Germany and the world face today - from mitigating climate change to the shortage of skilled labor- will require concerted, transformative political effort that builds on collective values and pursues societal goals. Economic growth should beachieved in a sustainable and inclusive manner and not at the expense of social cohesion or future generations. To do this, we need to rethinkprosperity and find new ways to measure it. Productivity growth and material gains, measured in terms of gross domestic product (GDP), are im-portant, but insufficient as central targets and yardsticks for social progress. The things that we actually value should be measured. This includesnot only economic well-being and income distribution, but also other dimensions of well-being, such as social participation, societal cohesion,personal empowerment and opportunity, as well as environmental sustainability. In this article, we discuss Germany's strategy for measuring andimproving multidimensional, sustainable prosperity, and propose ways to rethink and design new measures of economic and social prosperitythat encompass not only material prosperity and economic output, but also the social and environmental dimensions of prosperity.
Keywords: A13; D63; E21; I30; O15; O44; 330